Radiation Plus Anti-PD-1 Therapy for NSCLC Brain Metastases: A Retrospective Study - Liao, Guixiang; Qian, Yuting; Arooj, Sumbal; Zhao, Zhihong; Yan, Maosheng; Li, Zihuang; Yang, Hongli; Zheng, Tao; Li, Gang; Li, Xianming; Khan, Muhammad (Frontiers in Oncology, 2021)
Background Radiation therapy (RT) is the mainstay of brain metastases (BMs), and anti-PD-1 blockade has led to intracranial responses in non-small cell lung carcinoma (NSCLC) patients with brain BMs. Objective This study aimed to evaluate the efficacy and safety of adding anti-PD-1 blockade to RT in the management of NSCLC patients with BM in terms of survival outcome. Materials & Methods We retrospectively reviewed 70 NSCLC patients with BMs who were treated with whole brain radiation therapy (WBRT) between January 2016 and January 2021. Of the 70 patients, 29 additionally received anti-PD-1 therapy within 30 days of WBRT initiation. Baseline characteristics of the patients and efficacy outcomes such as progression-free survival (PFS) and overall survival (OS) were statistically compared using SPSS v26. Results were obtained using the Chi-square test/Fisher exact test, t-test, Kaplan-Meier, and Cox regression survival analyses. Results The median survival for the entire cohort was 24 months (95% CI, 19.5–28.5). The median survival times for WBRT alone and WBRT plus anti-PD-1 therapy cohorts were 20 months (95% CI, 11.6–28.3) and 27 months (95% CI, 19.5–28.5), respectively (p=0.035). There was no statistical difference in PFS for the treatment cohorts (median PFS for WBRT alone: 7 months vs. 12 months for WBRT plus anti-PD-1, p=0.247). In EGFR wild-type subgroup (n=31), both PFS (p=0.037) and OS (p=0.012) were significantly improved. Only the treatment group (WBRT plus anti-PD-1) was a significant predictor of OS on univariate and multivariate analyses (p=0.040). There were no significant differences in adverse events among the treatment groups. Conclusions NSCLC patients with BM receiving additional anti-PD-1 therapy may derive better OS than WBRT alone without any increase in adverse events. Prospective well-designed studies are warranted to validate and elucidate the additive effects of the two modalities in this group of patients.